THE POTENTIAL OF SECANG WOOD DECOCTION AS AN ODOR CONTROL FOR DIABETIC FOOT ULCER : POTENSI AIR REBUSAN KAYU SECANG SEBAGAI PENGONTROL BAU ULKUS KAKI DIABETIK - Harli, Kurnia; Irfan; Azzahra, Siti Fatimah; Mursyid, Aco; Febrianti, Nur Auliyah; Bauk, Ikram (Jurnal Kesehatan, 2024)
Diabetic foot ulcers are a serious complication that can significantly affect the quality of life for individuals with diabetes. One common issue associated with diabetic foot ulcers is the presence of unpleasant odors. This study aims to investigate the potential of secang wood decoction as an effective odor control for diabetic foot ulcers. This research follows an experimental design with pre-test post-test control group. The study sample consists of 32 patients with diabetic foot ulcers, randomly assigned to two groups. The treatment group received wound cleansing with secang wood decoction, while the control group was washed with a 0.9% NaCl solution. The results indicated a significant reduction in odor intensity both treatment and control group. This research concludes that secang wood decoction demonstrated potential effectiveness in controlling odors associated with diabetic foot ulcers. These findings suggest that secang wood decoction holds promise as a natural and accessible method for managing odor in diabetic foot ulcers. Further research is needed to explore its long-term effects and potential side effects. Additionally, studies with larger sample sizes and diverse populations would provide more comprehensive insights into the effectiveness and safety of secang wood decoction as an odor control measure for diabetic foot ulcers.